Реабілітація імунологічного статусу пацієнтів після радикального лікування онкопатології бальнеотерапевтичним комплексом Трускавця - Івасівка, С.В.; Білас, В.Р.; Ходак, О.Л. (Інститут фізіології ім. О.О. Богомольця НАН України, 2003)
Обследовано 60 прооперированных онкологических больных в динамике бальнеологической терапии. Изучено показатели неспецифической, клеточной и гуморальной иммунореактивности в периферической крови больных. Установлено повышение количественных характеристик популяций и субпопуляций лимфоцитов, натуральных киллеров, фагоцитарной активности нейтрофилов. Есть все основания считать, что санаторно-курортное лечение полезно на этапе реабилитации онкологических больных. Balneology treatment was investigated in 60 сancer patients after radical therapy. The results of the study about non-specifity, cellular and humoral immunity in peripheral blood are presented. Normalisation of disbalance in smmunoregulative subpopulations of T-lymphocytes, immunocompetents cells and evaluation of phagocytic function was shown. Such studies received us speac that balneology reatment in patients with advanced cfncer increased the effectiveness of clinical and immune rehabilitation.